Modelling distributed energy resources in energy service networks - Acha, Salvador (IET renewable energy series ;, 2013)
The book presents a modelling framework for integrated steady-state optimisation of energy service networks under the presence of embedded technologies; time-coordinated optimal power flow for energy service networks; on load tap changers; combined heat and power generation and; modelling electric vehicle mobility on energy service networks.